Building a Peace Economy? Liberal peacebuilding and the development-security industry - Peterson, Jenny H. (New Approaches to Conflict Analysis, 2014)
This book critically examines the range of policies and programmes that attempt to manage economic activity that contributes to political violence. It offers a new framework for understanding both the problem of economic activity in conflict zones as well as programmes aimed at managing these and transforming them into more peaceful economic and political relationships. Through this examination, both the problems of liberal modes of peacebuilding, implemented by the development-security industry, and opportunities for policy innovation are explored.Useful charts and frameworks throughout the book provide the reader with a range of analytical tools that can be easily used to explore war economies and related policies in a range of contexts, making this book an essential read for students, policy makers and aid practitioners working in a range of disciplines and conflict-affected areas.